ARTIFICIAL INTELLIGENCE USAGE AND ACADEMIC PERFORMANCE OF CME AND CASE STUDENTS - Abiner, Angel Rose A. (President University, 2024)
The focus of the study was to determine the relationship between artificial intelligence usage and academic performance in two different fields: the College of Marine Engineering (CME) and the College of Arts, Science, and Education (CASE). Descriptive correlational method and researcher-made questionnaire was used to gather the data of this study. The respondents were the one hundred seventy-nine (179) the 1st year and 2nd year students of the College of Maritime Education and the thirty-focus (34) College of Arts, Sciences, and Education departments of the Colegio de la Purisima Concepcion enrolled in the first semester of the academic year 2023-2024. The data gathered were analysed using the frequency, percentage and mean as descriptive statistics, t-test and Pearson r for correlational inferential for determining the significant associations of the dependent and independent variables. The study shows that there is no significant difference in the level of artificial intelligence when grouped according to age, sex, year level, and course program. Students in CME and CASE were both using artificial intelligence results as high. For the students in both course program artificial intelligence is very helpful when it comes to their study. There is a significant relationship between the level of artificial intelligence usage and the academic performance of students. The Pearson’s r value of 0.358 and a significance value of 0.000 (lower than the alpha level of 0.05) lead to the rejection of the null hypothesis, indicating a significant relationship between these variables. Additionally, the conclusion drawn, stating that “the higher the level of artificial intelligence usage, the higher the level of academic performance of students.’ This suggest that as the level of AI usage increase, there’s a tendency for academic performance to increase as well.